Evaluating the Potentials of Open Source in Medical Field: Are We Ready to Embrace it? - Jha, Jay Prakash (Journal of Karnali Academy of Health Sciences, 2023)
Open source software has gained significant traction in recent years, along with some concerns. Here we discuss the features open source model like greater transparency, cost-effectiveness, and customization. It also addresses the rising concerns on privacy and security issues in internet. This article highlights the benefits and limitations of open source software in medical services and health education.